PENGARUH PERENCANAAN PAJAK TERHADAP MANAJEMEN LABA DENGAN ARUS KAS OPERASI SEBAGAI VARIABEL KONTROL - Hapsari, Denny Putri; Manzilah, Dwi (JAK (Jurnal Akuntansi) : Kajian Ilmiah Akuntansi, 2016)
This study aims to determine the effect of tax planning, to earnings management with operating cash flow as control variable at companies manufacturing Company Sub Sector of the automotive and components  in Indonesia Stock Exchange period (BEI) 2011- 2015.  This research was conducted using the method of literature study and documentation. The population in this study amounted to 13 companies and sampling using purposive sampling as a technique to collect data. The number of samples collected were 6 companies. The method used is descriptive quantitative   and data analysts using descriptive statistics, classical assumption test, simple regression analysis, partial correlation analysis and hypothesis testing. The data in this study were processed using SPSS version 21.  The results of this research on the statistical significance test (T-test) showed that the tax planning significantly effect on earnings Management. The partial correlation analysis shows that tax planning and earnings management in have influence effect on operating cash flow as control variable on activity   Keywords: Tax Planning, Earnings Management and  Operating cash flow